The influence of Islamic culture on information privacy: case of Malaysia’s computer professionals - Wan Abdul Rahim Wan Mohd Isa; Ahmad Iqbal Hakim Suhaimi; Nurulhuda Noordin; Mohd Sabry Mohd Safiq (Institute of Advanced Engineering and Science, 2020)
In today's era of vulnerability and volatility, technologies in an organization evolving faster than the traditional landscape. Thus, sets the stage for trust and privacy concern for all the data that flying around in the database. Research on cultural aspects toward privacy starting to attract more ongoing research effort especially in Islamic religious culture. Islam gives great importance to the fundamental human right to privacy. This study aims to investigate Islamic cultural influences on Malaysia's computer professionals' self-regulatory efficacy towards the protection of personal information privacy by adapting the research frameworks of previous works. Further, data for this research obtained through the survey with computer professionals. Out of 226 respondents, 208 data are valid and usable for this study. Spearman's Rank Order Correlation was used to determine the relationship between culture and Information privacy self-regulatory efficacy dimensions. The findings from this research could provide a better understanding of the subject matter and be used as the basis for future studies.